Structural Vaccinology for Viral Vaccine Design - Anasir, Mohd Ishtiaq; Poh, Chit Laa (Frontiers in Microbiology, 2019)
Although vaccines have proven pivotal against arrays of infectious viral diseases, there are still no effective vaccines against many viruses. New structural insights of the viral envelope, protein conformation and antigenic epitopes can guide the design of novel vaccines against challenging viruses such as human immunodeficiency virus (HIV), hepatitis C virus, enterovirus A71 and dengue virus. Recent studies demonstrated that the applications of these structural information can solve some of the vaccine conundrums. This review focuses on recent advances in structure-based vaccine design, or structural vaccinology, for novel and innovative viral vaccine design.